2014
DOI: 10.1093/annonc/mdt525
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment efficacy in primary inflammatory breast cancer by hormonal receptor- and HER2-defined subtypes

Abstract: Hormone receptor and HER2 molecular subtypes had limited predictive and prognostic power in our IBC population. All molecular subtypes of IBC had a poor prognosis. HR-positive status did not necessarily confer a good prognosis. For all IBC subtypes, novel, specific treatment strategies are needed in the neoadjuvant and adjuvant settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
93
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 14 publications
13
93
6
Order By: Relevance
“…These results are in keeping with those of the NOAH trial (10), a randomized phase III trial evaluating neoadjuvant trastuzumab in patients with HER2-positive locally advanced breast cancer, recently updated (26) The results of BEVERLY-2 are encouraging as IBC is a rare yet aggressive form of breast cancer, and has poor prognosis (27). Chemotherapy-induced pCR rates were historically low in that setting, ranging from 20% to 30% (9,28,29). Over the past decade, clinical trials have demonstrated incremental improvements in outcome for patients with IBC.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These results are in keeping with those of the NOAH trial (10), a randomized phase III trial evaluating neoadjuvant trastuzumab in patients with HER2-positive locally advanced breast cancer, recently updated (26) The results of BEVERLY-2 are encouraging as IBC is a rare yet aggressive form of breast cancer, and has poor prognosis (27). Chemotherapy-induced pCR rates were historically low in that setting, ranging from 20% to 30% (9,28,29). Over the past decade, clinical trials have demonstrated incremental improvements in outcome for patients with IBC.…”
Section: Discussionsupporting
confidence: 72%
“…The use of pCR as a prognostic marker for DFS and OS in patients treated by neoadjuvant therapy is supported by several lines of evidence (12,13), including recent reports in HER2-positive breast cancer (9,(14)(15)(16). A noticeable dissociation was however observed in non-IBC with bevacizumab, which increased the pCR rate in the neoadjuvant setting (17,18) but had no impact on survival in the adjuvant setting of HER2-positive breast cancer (19,20).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although IBC comprises <5% of breast cancer cases, the tumor accounts for more than 10% of breast cancer mortality in the United States (2,3). IBC is considered aggressive because it evolves rapidly-over days to weeks rather than months-with most patients presenting with lymph node involvement and more than 30% of patients having distant metastases at diagnosis (4,5). Although IBC, like non-IBC breast cancers, is a heterogeneous disease and can occur as any of the five molecular subtypes, the IBC is most commonly ErbB2 overexpressing or triple negative (6), thus rendering a large armamentarium of targeted drugs ineffective.…”
mentioning
confidence: 99%
“…At the time of presentation, 55 to 85% of patients have regional lymph node metastasis clinically. 2 Despite improved survival in the past three decades because of the introduction of multimodality treatment approaches, the survival outcomes of patients with inflammatory breast cancer remain poorer compared with patients with noninflammatory, locally advanced breast cancer, 3,4 underscoring the need for understanding the biology of the disease and exploring new therapeutic targets.…”
mentioning
confidence: 99%